Avaliação de colesterol e triglicerídeos séricos em cães saudáveis suplementados com ômega n-3 - Machado, Luiz Henrique de Araújo; Santos, T. H. Y.; Lourenço, Maria Lúcia Gomes; Takahira, Regina Kiomi [UNESP] (My University, 2012)
The analysis of serum cholesterol and triglycerides was performed in 20 healthy mongrel dogs, 10 male and 10 female, before and after supplementation for 30 days with fatty acids of long chain polyunsaturated derived from omega-3 n (497mg docosahexaenoic acid and 780mg eicosapentaenoic acid). The serum cholesterol presented a significant reduction after supplementation in both sexes (271.6±79.8mg/dL; 236,2±67,6mg/dL, before and after supplementation respectively). Regarding serum triglycerides, there was a reduction only in females (57.8±12,1mg/dL; 45.2±7,8mg/dL, before and after supplementation respectively), with no effect of supplementation in males.

A análise da concentração sérica de colesterol e triglicerídeos foi realizada em 20 cães, sem raça definida, saudáveis, 10 machos e 10 fêmeas, previamente e após a suplementação por 30 dias com ácidos graxos poli-insaturados de cadeia longa derivados do ômega n-3 (497mg ácido docosa-hexaenoico e 780mg ácido eicosapentanoico). A concentração sérica de colesterol apresentou redução significativa após a suplementação em ambos os sexos (271,6±79,8mg/dL; 236,2±67,6mg/dL, antes e após suplementação, respectivamente). Em relação à concentração sérica de triglicerídeos, houve redução apenas nas fêmeas (57,8±12,1mg/dL; 45,2±7,8mg/dL, antes e após suplementação, respectivamente), não havendo efeito da suplementação nos machos.
Evaluation of serum cholesterol and triglycerides in healthy dogs supplemented with ômega-3 N
Keywords: Dog; Omega n-3; Cholesterol; Triglycerides; Cão; Ômega n-3; Colesterol; Triglicerídeos